2021
DOI: 10.17762/itii.v9i2.307
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Co-Worker Incivility Towards Deviant Behaviour: a Quantitative Study of Casual Dining Restaurants Frontline Employees in the Klang Valley, Malaysia

Abstract: The past decade has seen a growing number of casual dining restaurants in Malaysia. This trend of consumption is due to modern lifestyle, socio-demographic, and social media influence. Nevertheless, restaurants struggle to maintain a productive work environment and report to have association with incivility and deviant behaviour which in long run create destruction. The aim of this paper is to examine the influence of co-worker incivility towards employees performing deviant behaviour with the moderating role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…Xiao et al (2023) and Guidetti et al (2021) contended that incivility exists because of the inability of management, supervisors and co-workers to organize activities in the workplace. Han, Harold, Oh, Kim, and Agolli (2022) see incivility as an abnormal behavior, and the violation of workplace norms with insufficient evidence to harm an individual Hassan (2021) showed that incivility at workplace is associated with chaos bedlam, pandemonium and disarray and it is partially due to the breaching of workplace culture and norm. Fundamentally, there are three partakers in workplace incivility -instigator, target and observer (Adil, Hamid, & Waqas, 2020;Khan, Elahi, & Abid, 2021;Razzaq, Bowra, & Khan, 2023); Therefore, in order for uncivil behaviour to manifest within the workplace, these three factors are involved in the overall process.…”
Section: Introductionmentioning
confidence: 99%
“…Xiao et al (2023) and Guidetti et al (2021) contended that incivility exists because of the inability of management, supervisors and co-workers to organize activities in the workplace. Han, Harold, Oh, Kim, and Agolli (2022) see incivility as an abnormal behavior, and the violation of workplace norms with insufficient evidence to harm an individual Hassan (2021) showed that incivility at workplace is associated with chaos bedlam, pandemonium and disarray and it is partially due to the breaching of workplace culture and norm. Fundamentally, there are three partakers in workplace incivility -instigator, target and observer (Adil, Hamid, & Waqas, 2020;Khan, Elahi, & Abid, 2021;Razzaq, Bowra, & Khan, 2023); Therefore, in order for uncivil behaviour to manifest within the workplace, these three factors are involved in the overall process.…”
Section: Introductionmentioning
confidence: 99%